(untitled) (Indian Journal of Animal Production and Management, 2013)
Cow urine has a unique place in Ayurveda and is suggested to improve general health of human being. Indigenous and hill cattle have a good quality urine as compared to crossbred cattle. So, present study was conducted utilizing primiparous lactating Hill cattle, Sahiwal and crossbred cattle maintained in Instructional Dairy Farm, GBPUAT, Pantnagar for comparing their urine constituents. Urine samples were collected early morning from four animals of each group at an interval of one month, with three repetitions and were estimated for pH, specific gravity, total solid per cent, ash per cent, total protein, urea and creatinine. There was significant difference (Pd”0.05) between chemical composition of Hill cattle urine with that of Sahiwal and crossbred cattle urine. Lower pH, specific gravity, total solids, urea, creatinine, total protein, and ash per cent were observed in urine of Hill cattle while as higher values were observed in crossbred cattle urine. There was a non-significant difference (Pd”0.05) in urea, creatinine, total protein, and ash per cent among Hill cattle and Sahiwal urine but a significant difference (Pd”0.05) with crossbred cattle urine.